Murder of Innocence - Patterson, James 1947-; DiLallo, Max; Bourelle, Andrew; Graybill, Stephen ([New York] : Hachette Audio, 2020)
It's impossible to resist Andrew Luster. He's rich, charming, and good-looking, and dozens of women have fallen under his spell. But Andrew is no mere womanizer. He's a predator, and it'll take a global effort to put him behind bars.
Keywords: Luster, Andrew; Murder -- Case studies -- United States; Murder -- Case studies -- Investigation -- United States; Murder; Murder -- Investigation; United States; Audiobooks; Case studies; Audiobooks